(untitled) (Educação e Pesquisa, 2015)
This paper discusses my efforts during several decades of research to understand the interaction of schooled literacy, language diversity, and social inequality. It draws on semiotic and Marxian traditions to investigate language diversity and social inequality in contemporary European and North American settings. Focusing especially on racialization practices and class dynamics, the arguments present early studies of minority language and schooling, which build toward and frame a recent study of federal education policy and immigrant experiences of schooling and language hierarchy. That study draws from sociolinguistic and ethnographic research among multilingual migrant families and communities in upstate New York, with particular focus on children’s experience with multilingual repertoires and monolingual language polices in schooling (COLLINS, 2012). Examining federal education policy and debates and comparing classroom interaction processes involving different ethnolinguistic groups, I identify two “state effects” (TROUILLOT, 2001) as they operate across different institutional sites. I argue that such effects are ways in which contemporary states attempt to regulate globalized class and racial dynamics. By shaping educational subjects whose social and linguistic characteristics, and especially their class characteristics, are both obscured and employed in school-related categorizations and school-based communicative processes, such effects contribute to the hegemonic reproduction of social, linguistic and educational inequalities (HYMES, 1996; MENKEN, 2008).